Efficient certificateless sequential multi-signature scheme - Yan-lin QIN; Xiao-ping WU (Tongxin xuebao)
The authentication of recommendation information transmitted through trust train is important for trust model in distributed environment. To solve this problem, the security model for the certificateless sequential multi-signature scheme was studied and then a certificateless sequential multi-signature scheme using elliptic curve cryptography and bi-linear pairings was proposed. It is proven in the random oracle that the security of the scheme is based on the fact that the computational Diffie-Hellman problem is hard. Meanwhile, the scheme needs no certificate management center and the length of signature is independent of the number of signers. It needs no bilinear pairing operation in the phase of partial signing, and just needs one each in verification phases of partial signing and integral signing. So it is computationally ef-ficient compared to the existing signature schemes and can be applied conveniently to trust transitivity in large scale dis-tributed environment.